Financial Reporting Quality’s Moderating Effects on The Relationship Between External Auditing Practices and Firm Performance During a Decline in Covid-19 (Raparin Journal of Humanities (RJH), 2024)
This research article explores the moderating role of financial reporting quality in the relationship between external auditing practices and firm performance during a decline in the COVID-19 pandemic. Using 212 questionnaire responses from small to medium manufacturing companies situated in industrious locations in Erbil, Erbil Industrial Zone, Erbil Free Zone, Sheikh Choly Industrial Area, and Qushtapa Industrial Area of Kurdistan, a structural equation model was estimated. The study findings are threefold and have advanced empirical ideas by highlighting that (1) the adoption of external practices has a significant effect on financial reporting quality and an insignificant positive effect on firm performance, (2) the adoption of financial reporting quality has a significant positive effect on firm performance and (3) financial reporting quality has a moderating effect on the relationship between external auditing practices and firm performance during a decline in Covid-19. The findings contribute to the advancement of the Principal-Agent Theory by providing empirical evidence on how external auditing practices influence financial reporting quality, aligning with the expectations of agency theory. It enriches the theoretical understanding of how monitoring mechanisms impact the agent’s behavior in the principal-agent relationship. To enhance firm performance, the findings suggest that it is important for firms to recognize the link between financial reporting quality and firm performance and allocate resources and efforts to improve reporting practices accordingly.